2013
DOI: 10.1007/s13277-013-1177-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum carbohydrate antigen 19-9 and prognosis of patients with gastric cancer

Abstract: Previous studies have assessed the prognostic role of serum carbohydrate antigen 19-9 (CA 19-9) concentration in patients with gastric cancer, but the findings from those studies were inconsistent. We searched the PubMed and Web of Science databases to find eligible studies assessing the prognostic role of CA 19-9 in patients with gastric cancer. Twelve studies with a total of 5,072 gastric cancer patients were finally included into the meta-analysis. The pooled hazard ratio (HR) with corresponding 95 % confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…However, Kodera et al (Kodera et al, 1996) revealed that serum CA 19-9 was better than CEA as a prognostic factor in multivariate analyses in gastric cancer patients. A meta-analysis performed by Xiao et al (Xiao et al, 2014) showed that elevated serum CA 19-9 levels were associated with poorer overall survival in patients with gastric cancer. In our study, the univariate analysis indicated that there was a significant difference in 5-year survival between positive and negative cases for each of the four markers examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kodera et al (Kodera et al, 1996) revealed that serum CA 19-9 was better than CEA as a prognostic factor in multivariate analyses in gastric cancer patients. A meta-analysis performed by Xiao et al (Xiao et al, 2014) showed that elevated serum CA 19-9 levels were associated with poorer overall survival in patients with gastric cancer. In our study, the univariate analysis indicated that there was a significant difference in 5-year survival between positive and negative cases for each of the four markers examined.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of factors have been recognized as prognostic factors for early gastric cancer, including tumor size, differentiation status, tumor depth, LNM and vessel involvement [ 7 ]. In addition, tumor markers including CEA [ 8 ], CA19–9 [ 9 ], and AFP [ 10 ] were demonstrated to be prognostic factors for gastric cancer. However, prognostic significance of these markers for early gastric cancer have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors are well recognized as prognostic indicators for gastric cancer, including tumor size, tumor depth, lymph node metastasis (LNM), and vessel involvement [ 3 , 4 ]. In addition, elevated levels of preoperative tumor markers, including CEA [ 5 ], CA19-9 [ 6 ], AFP [ 7 ], and CA125 [ 8 ], were demonstrated to be associated with gastric cancer prognosis. However, the prognostic values of these tumor markers within the normal range have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%